Legal power versus legal rights: isolation and quarantine of infectious diseases in Nigeria (2018)
Citizens expect and the law requires that governments take steps to protect their populations from infectious diseases. Yet, many of the controls that governments use to identify, prevent, and respond to infectious diseases limit individuals ‘ liberty of movement, privacy, freedom to travel as well as freedom to control their own bodies. The state has to strike a balance between individual control and acts for the public good. The 1926 Quarantine Act and the 1999 Nigerian Constitutions are the laws enabling the imposition of quarantine and isolation. The Act is however obsolete and unable to meet with the present day demands as it relates to public health emergencies. This paper concludes on the dire need to repeal the Act and enact a dynamic legislation that can meet up with technological advances of the 21s' century, and recommends some salient features which the legislation ought to have